Exploring the Loading Capacity of Generation Six to Eight Dendronized Polymers in Aqueous Solution. Issue 17 (6th July 2016) - Maltar‐Strmečki, Nadica; Yu, Hao; Messmer, Daniel; Zhang, Baozhong; Schlüter, A. Dieter; Hinderberger, Dariush
Abstract: Aspects of size, structural (im)perfection, inner density, and guest molecule loading capacity of dendronized polymers (DPs) of high generation (6≤ g ≤8) in aqueous solution are studied using electron paramagnetic resonance spectroscopy on amphiphilic, spin‐labeled guest molecules. The results show that the interior of the charged DPs is strongly polar, especially in comparison to their lower generation (1–4) analogues. This is a direct sign that large amounts of water penetrate the DP surface, reflecting the structural (im)perfections of these high‐generation DPs and much lower segmental densities than theoretically achievable. Images obtained with atomic force microscopy reveal that the high‐generation DPs do not aggregate and give further insights into the structural imperfections. Electron paramagnetic resonance spectroscopic data further show that despite their structural imperfections, these DPs can bind and release large numbers of amphiphilic molecules. It is concluded that attention should be paid to their synthesis, for which a protocol needs to be developed that avoids the relatively large amount of defects generated in the direct conversion of a generation g =4 DP to a generation g =6 DP, which had to be used here. Abstract : Nobody′s perfect : Aspects of size, structural imperfection, water content, and guest loading capacity of dendronized polymers of high generation (6≤ g ≤8) in aqueous solution are studied using atomic force microscopy and electron paramagnetic resonance spectroscopy on bound amphiphilic, spin‐labeled guest molecules.